REVITALIZATION OF KAWALI FOLKLORE IN THE FORM OF 2D ANIMATED DIGITAL STORYTELLING AS A MEDIUM FOR ORAL LITERATURE LEARNING AT THE COMMUNITY READING PARK OF CIAMIS REGENCY - Andri Noviadi; Sri Mulyani; H.R. Herdiana; Meisa Syaidah Hufa; Chindi Febrianti (Universitas Swadaya Gunung Jati, 2026)
This research addresses the erosion of Kawali folklore by transforming it into 2D animated digital storytelling, aiming to preserve local culture and provide engaging oral literature learning media, particularly for Community Reading Gardens (TBM) in Ciamis Regency. The research adopted the Research and Development (R&D) method, encompassing phases from data collection and script adaptation to 2D animation production using Toon Boom Harmony and Adobe After Effects. The primary finding was the documentation and selection of